Effect of Systemic Adenosine on Pain and Secondary Hyperalgesia Associated With the Heat/Capsaicin Sensitization Model in Healthy Volunteers. Issue 5 (1st September 2001) - Dirks, Jesper; Petersen, Karin L.; Rowbotham, Michael C.; Dahl, Jørgen B.
Abstract : Background and Objectives: Adenosine is an endogenous compound that may have analgesic effects. Results from clinical trials are not consistent, however, and there is a need for large-scale, randomized, placebocontrolled studies to clarify the role of adenosine in the treatment of pain states, including acute nociceptive pain and pain involving central sensitization. Methods: The analgesic and antihyperalgesic effect of systemic adenosine on the heat/capsaicin sensitization model of experimental pain was investigated in 25 healthy human volunteers. Sensitization was produced by heating the skin to 45°C for 5 minutes, followed by a 30-minute application of 0.075% capsaicin cream, and maintained by periodically reheating the sensitized skin to 40°C for 5 minutes at 40-minute intervals. Subjects received intravenous adenosine 60 μg/kg/min or saline for 85 minutes. Areas of secondary hyperalgesia to von Frey hair and brush stimulation, heat-pain detection thresholds (HPDTs) in normal and sensitized skin, and painfulness of stimulation with 45°C for 1 minute (LTS) in normal skin were quantified before, during, and after study drug infusion. Results: Systemic adenosine had no effect on the area of secondary hyperalgesia to von Frey hair or brush stimulation, HPDT in normal or sensitized skin, or painfulness of LTS in normal skin. Conclusion: We conclude that adenosine has no effect on acute nociceptive pain induced by heat stimulation or on secondary hyperalgesia induced by heat/capsaicin sensitization in healthy volunteers.